Philosophical and Psychopathological Perspective of Exile: On Time and Space Experiences - Silva Rojas, Matías; Armijo Nuñez, Julio; Nuñez Erices, Gonzalo (Frontiers in Psychiatry, 2015)
This article addresses the experience of exile from an interdisciplinary perspective (philosophy and psychiatry). The main purpose is to try to understand the experience of exile by rehearsing a psychopathological perspective to address it, so it can help with the treatment of disorders that come with this experience. Furthermore, the article tries to explore the experience and reflection of philosophers and thinkers who, being exiled themselves, tried to understand and explain this radical human experience, focusing on the experience of time and space.